PERANCANGAN CATU DAYA PORTABEL UNTUK PEDAGANG KELILING (Designing of Portable Power Supplay For Pitchman) - Mahlinda, Mahlinda; Rifki, Rifki (Baristand Industri Banda Aceh, 2016)
This paper presents the designing of portable power supply for pitchman.This equipmenthas functions as a electrical power provider, especially for pitchman as a replacement of electricalgenerator machine. This portable power supply consists of DC battery 12 volt 60 Ah, automatic batterycharger 16 volt 5 ampere, power inverter DC-AC 500 watt and relay 220 volt. When the unit connected toelectrical networks, the automatic battery charger generated 13,5 volt direct current (DC) which can becharging a 12 volt 60 Ah battery and automatically reducing the charging current to a low level wheneverthe battery is full charged. The 300 watt inverter was used to convert the direct current (DC) to alternatecurrent (AC). This electrical storages can be use to power on electric lamps for lightening to thepicthman at night. Test result showed, the automatic battery charger was able to charging the batterysuccessfully with maximum output 13,45 volt DC. The inverter was then tested with a 230 V 18 W softlight (SL) lamp and it was able to power on successfully with an output AC voltage of 236 volt for 34hours.